Attribution theory in the organizational sciences - Martinko, Mark J. (Henry Stewart Talks, 2014)
Definition of attributions, The attribution process, Attribution dimensions, Locus of causality, Stability, Leadership and attributions, Attribution styles, Optimistic attribution style, Pessimistic attribution style, Self-attribution styles, Social attribution styles, Attribution biases, Leader-member relations, Learned helplessness, Abusive supervision, Empowerment, Aggression, Counterproductive behaviour, Individual differences, Future directions